NANCY MACKAY, Curating Oral Histories: From Interview to Archive - Chernevych, Andrew (Archivaria, 2019)
Curating Oral Histories: From Interview to Archive. Nancy MacKay. Walnut Creek, CA: Left Coast Press, 2016. xv, 225 pp. ISBN 978-1-61132-856-1